Chatgpt-Ai Technology in Teaching Arabic for Specific Purposes from the Arabic Expert’s Perspective - Yuslina Mohamed; Wan Azura Wan Ahmad; Zainurrijal Abd Razak; Sulaiman Ismail; Mohamed Haji Ibrahim; Zulkipli Md Isa (Usuli Faqih Research Centre PLT., 2024)
Vol. 32 No. 2